Spatial distribution of kalantas (Toona calantas Merr. & Rolfe) in the Molawin-Dampalit Watershed, Mount Makiling Forest Reserve, Philippines - Castillo, Leilani A. (Ecosystems & Development Journal: a Journal on Tropical Forests and Natural Resources, 2015)
Vegetation inventory using a combination of point center method strip and quadrat method was conducted to determine the spatial distribution and population of kalantas (Toona calantas Merr. & Rolfe) in the Molawin–Dampalit Watershed of Mount Makiling Forest Reserve (MMFR). From the 1,081 individuals recorded in the 13 sampling plots established in three zones, 146 (13.3%) individuals are T. calantas, 51(35%) of which are trees and saplings and the remaining 95 (65%) individuals are seedlings. Majority of the seedlings are spread out within 20 m from the mother tree and between 164 to 480 masl. Beyond 20 m, there were very few seedlings found indicating close seed dispersal of T. calantas. Distribution of T. calantas increases at higher elevation. The highest number of seedlings (65) was recorded at an altitude of 480 masl while the highest number of trees and saplings (15) was recorded at an altitude of 370 masl. Sampling plots at higher elevation have less dense vegetation and therefore have more space for light penetration which is favorable to the growth of T. calantas. Additionally, higher elevations are less accessible to people and are therefore less disturbed. T. calantas showed a low population in terms of frequency, abundance and dominance as compared with other species. As a critically endangered species, this paper proposes to use these parameters as bases for restoring the population of T. calantas in Mt. Makiling. Since it is important to conserve reproductive trees in order to ensure continuous increase and perpetuity of the population, priorities will be given to those areas where mother trees exist. Conservation efforts are recommended for plots with mother trees and containing the highest number of seedlings